Can people-centered community-oriented interventions improve skilled birth attendance? Evidence from a quasi-experimental study in rural communities of Cambodia, Kenya, and Zambia - Anbrasi Edward; Aparna Krishnan; Grace Ettyang; Younghee Jung; Henry B. Perry; Annette E. Ghee; Jane Chege (BMC, 2020)
Abstract Background Skilled attendance at delivery is a key marker for reducing maternal mortality. Effective community engagement strategies complemented by community health worker (CHW) services can improve access to maternal health services in areas with limited health infrastructure or workforce. Methods A quasi-experimental study with matched comparison groups was conducted in Cambodia, Kenya and Zambia to determine the effect of integrated community investments on skilled birth attendance (SBA). In each country, communities in two districts/sub-districts received a package of community-oriented interventions comprised of timed CHW household health promotion for maternal, newborn and child health complemented by social accountability mechanisms using community scorecards. Two matched comparison districts/sub-districts received ongoing routine interventions. Data from the final evaluation were examined to determine the effect of timed CHW services and community-oriented interventions on SBA. Results Over 80% of the 3037 women in Cambodia, 2805 women in Kenya and 1171 women in Zambia reported SBA. Women in intervention sites who received timely CHW health promotion and social accountability mechanisms in Cambodia showed significantly higher odds of SBA (aOR = 7.48; 95% CI: 3.87, 14.5). The findings also indicated that women over the age of 24 in Cambodia, women with primary or secondary education in Cambodia and secondary education in Kenya, women from higher wealth quintiles in Cambodia, and women with four or more antenatal care (ANC) visits in all countries reported significantly higher odds of SBA. Inclusion of family members in pregnancy-related discussions in Kenya (aOR = 2.12; 95% CI: 1.06, 4.26) and Zambia (aOR = 6.78; 95% CI: 1.15, 13.9) and follow up CHW visits after a referral or health facility visit (aOR = 2.44; 95% CI: 1.30, 4.60 in Cambodia; aOR = 2.17; 95% CI 1.25, 3.75 in Kenya; aOR = 1.89; 95% CI: 1.05, 2.02 in Zambia) also showed significantly greater odds of SBA. Conclusions Enhancing people-centered care through culturally appropriate community-oriented strategies integrating timely CHW health promotion and social accountability mechanisms shows some evidence for improving SBA during delivery. These strategies can accelerate the achievement of the sustainable development goals for maternal child and newborn health.